Corporate Social Accounting (Book). - Mobley, Sybil C.; Spiller, Earl A. (The Accounting Review, 1975)
Abstract Reviews the book 'Corporate Social Accounting,' edited by Meinolf Dierkes and Raymond A. Bauer.